Respuestas

2012-10-06T20:12:06+02:00

a)

x-x1/x2-x1=y-y1/y2-y1

x-3/5      = y-7/-13

(x-3)*(-13)  = (y-7)* 5

-13x+39      =  5y-35

-13x+74      = 5y

-13/5x + 74/5 =  y            <<<<ECUACION DE LA RECTA

 

LA PENDIENTE ES -13/5.

 

x-x1/x2-x1=y-y1/y2-y1

x-2/-1      = y-8/-8

(x-2)*(-8)  = (y-8)* -1

-8x+16      =  -y+8

-8X+8/-1   =  y

 8X-8        = Y

 

LA PENDIENTE ES 8

 

x-x1/x2-x1=y-y1/y2-y1

(x+5)*(-8)  = (y-6)* 4

-8X-16       = 4y

-8X-16/4    = y

-2x - 4  =y

 

LA PENDIENTE ES -2